Folic Acid Supplementation as Preeclampsia Prevention on Pregnant Women in Indonesia - Felicia, Devi; Chikita Fredy, Felix; Jayadi Iskandar, William (The Journal of The Indonesian Medical Students Association, 2010)
The health of mother and child is still a major problem in Indonesia. It is depicted in the high mother and neonatal mortality rate in Indonesia, which is the highest among other countries in South East Asia. In addition, the rate is still far away from the MDG (Millenium Development Goal) 2015 target.Preeclampsia, which is still reported to be the main complicating factor of pregnancy in Indonesia, is a major threat to the mothers life, as well as the infantss. Obviously, it is contributes to the high mother and neonatal mortality rate in Indonesia. In the other hand, preeclampsia can be prevented, one of which is by folic acid supplementation.Researchers have proved that folic acid supplementation can lower homocysteine level, the excessive level of which is a risk factor of preeclampsia. Through folic acid supplementation, it is expected that the frequency of preeclampsia, and consequently, the mother and infant mortality rate will be decreased.Key words: preeclampsia, homocysteine, folic acid supplementation